The Influence of Stadium Attributes on Stadium Loyalty Development within the Context of Saudi Arabia - Badr Fallatah (College of Physical Education and Sport Sciences, 2023)
Although soccer has become vastly popular on a global scale as evident in the constant setup of new leagues and teams worldwide, there are critical issues that primarily regard attendance rates at live soccer matches. This is due to low attendance rates, specifically in comparison to the capacity of stadiums. Therefore, it is important to investigate factors and attributes that can potentially resolve such issues. Thus, this study investigates stadium attributes as predicting factors of stadium loyalty in Saudi Arabia. Especially in Saudi Arabia where soccer is considered as the national sport, with huge financial inflow towards soccer infrastructure, there remain the issues of low attendance rate and utilization of soccer stadiums. Thus, by theorizing constructs and related hypotheses based on the extant literature and further accessing them through SEM, we were able to prove not only the hypothesized relations, but also drew out the important implications for both the theoretical and practical domains in Saudi Arabia and countries of the Gulf region. Keywords: Stadium Loyalty, Social Interaction, Entertainment Experience, Team Involvement